2020
DOI: 10.29082/ijnms/2020/vol4/iss3/324
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Husband Support of Anemia Management With Incidence Anemia in Pregnancy

Abstract: Anemia during pregnancy caused death in the mother and fetus. Husband's support for reduction the risk of anemia during pregnancy was important. The purpose study was to determine relationship husband's support of anemia management with the incidence anemia in pregnant.  Design research used analytic correlation with a cross-sectional. The population were third trimesters  pregnantcy in Mojokerto City. Sample size were 54 pregnant women with purposive sampling. Independent variabel was husband support. Depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Research on husbands' support of young mothers' motivation in exclusive breastfeeding showed that most husbands (92.3%) provided good support [23]. Good support from the husband motivates young mothers to behave well in practicing exclusive breastfeeding [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on husbands' support of young mothers' motivation in exclusive breastfeeding showed that most husbands (92.3%) provided good support [23]. Good support from the husband motivates young mothers to behave well in practicing exclusive breastfeeding [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a family with a pregnant woman, the husband is expected to motivate, help, and accompany. The husband is also responsible for making her feeling comfortable and calm when there are problems in her pregnancy [19].…”
Section: Introductionmentioning
confidence: 99%